Acoustic Forceps Based on Focused Acoustic Vortices with Different Topological Charges - Du, Libin; Hu, Gehao; Hu, Yantao; Wang, Qingdong (Sensors (Basel, Switzerland), 2023)
For enhanced energy concentration with improved flexibility for object manipulation, a focused acoustic vortex (FAV) is designed using a sector planar piston transducer array and acoustic lens that can produce the effective concentration of the acoustic field to perform the focusing function. Compared to the Gaussian beam, which tends to cause the object to deviate from the axis of acoustic propagation, FAVs can form a central valley region to firmly bind the objects, thus preventing off-target effects. The heat energy in the paraxial region is transferred to the vortex center in the form of heat transfer so that the temperature-sensitive liposomes captured can quickly release drugs, which has a good effect on targeted drug administration. The focused acoustic wave stopped acting on the tissue (gel) for 2 s, the temperature of the vortex center continued to rise, reaching 41.5 °C at the moment of 3.7 s, at which point the liposomes began to release the drug. The FAVs capture the drug and use its thermal effect to achieve accurate and rapid treatment. The simulation results show that the drug release temperature of temperature-sensitive liposomes can be achieved by controlling the action time of the vortices. This study provides a reliable theoretical basis for the clinical application of targeted drugs.